Nypa fruticans wurmb (Mangrove Palm) Fruit Kernel: Effect on physicochemical, sensory evaluation and shelf-life of wheat biscuits - Md. Ripaj Uddin; Md. Salim Khan; Md. Khairul Islam; Muhammad Abdullah Al Mansur; Md. Selim Reza; Md Hamedul Islam; Mehedi Hasan; Sharmin Ahmed; Sirajum Monira; Abubakr M. Idris (PLoS ONE, 2026)
The global biscuit market is shifting towards healthier, gluten-free options, demanding novel and sustainable ingredients. This research introduces Nipa palm kernel flour (NFK) an underutilized, gluten-free resource from the mangrove Nypa fruticans Wurmb as a promising functional ingredient for biscuit production. Mature fruits were collected from the Sundarbans, Bangladesh, to develop nutritious snacks and valorize this sustainable resource from an underutilized plant. Kernels were extracted, blanched, dried, and milled into flour. Biscuits were formulated by substituting refined wheat flour with 0% (control), 10%, 20%, and 30% NFK. The physical, nutritional, sensory, and shelf-life properties of the biscuits were comprehensively analyzed using standard methods. NFK incorporation significantly improved the biscuit's nutritional profile. The 30% NFK biscuit exhibited a 38% reduction in fat, a seven-fold increase in crude fibre (from 0.19% to 1.35%), and a substantial boost in essential minerals, with iron content more than doubling to 53.3 mg/kg. Incorporating NFK significantly altered the biscuits’ color profile, reducing lightness (L : 65.30 to 55.40) and yellowness (b : 25.80 to ~22.50–23.10) while increasing redness (a*: 4.50 to ~5.85–6.10), resulting in a desirable, darker red-brown hue. Crucially, all NFK-enriched biscuits received high sensory acceptability scores (≥7.85 on a 9-point scale), with no significant difference in overall liking compared to the control. Microbiological analysis confirmed product safety and a shelf life of over 12 months. The incorporation of Nypa fruticans kernel (NFK) flour at 15% substitution significantly enhanced the biscuits’ functional profile, increasing total phenolic content by 212% (to 265.8 mg GAE/100g) and flavonoid content by 174% (to 89.1 mg QE/100g). This directly boosted antioxidant capacity, with DPPH IC₅₀ decreasing 3.3-fold (to 3.8 mg/mL) and FRAP value increasing 4.6-fold (to 8.2 mmol Fe 2 ⁺ /100g), transforming the biscuit into a potent bioactive food carrier. NFK is a promising gluten-free biscuit ingredient. Future research should confirm large-scale production, in-vivo bioavailability, and precise compound characterization, supporting sustainable mangrove use and healthy food choices.